Factors associated with health-related quality of life among government employees in Putrajaya, Malaysia - Mohd Ashri, Muhamad Hasrol; Abu Saad, Hazizi; Adznam, Siti Nur ‘Asyura (Multidisciplinary Digital Publishing Institute, 2021)
The current rapid growth of the economy has necessitated an assessment of health-related quality of life (HRQOL) and its associated factors among employees. Unfortunately, there are still limited data available in this area among the Malaysian working population in government sectors. The aim of this study was to evaluate the factors associated with HRQOL among government employees in Putrajaya, Malaysia. This cross-sectional study recruited 460 eligible government employees who worked in the area of Putrajaya through simple random sampling. The self-administered questionnaire was distributed to these participants to collect information on the SF-36 profile of scores, sociodemographic factors, lifestyle factors, and medical history. The results of this study signify that most of the participants were identified as having good HRQOL with the mean score of overall HRQOL was 72.42 ± 14.99. Multivariate analysis showed that being younger, receiving a better monthly personal income, a smaller household number, performing more physical activity, not having any chronic disease, and not using any long-term medication were significantly positively associated with overall HRQOL. The participants who did not have a family history of chronic disease were reported to be significantly associated with better mental component summary (MCS). Further, males were significantly positively associated with bodily pain (BP) and general health (GH) only, whereas better occupational status was limited to social functioning (SF). In conclusion, the results of this study provide motivation for future research and initiatives for improving the physical, emotional, and social well-being of government employees.